THE IMPORTANCE OF EYE TEST FOR SCREENING EYE DISEASES IN THE NEONATAL PERIOD: INTEGRATIVE REVIEW: THE IMPORTANCE OF EYE TEST FOR SCREENING EYE DISEASES IN THE NEONATAL PERIOD: INTEGRATIVE REVIEW - Freire Nascimento, Dulcy Dávyla; Lima Junior, Umberto Marinho de; Silva, Macerlane de Lira; Quental, Ocilma Barros de (Brazilian Journal of Production Engineering, 2020)
Introduction: The child's visual system develops potentially in the first year of life, so it is essential early investigations on visual acuity. In Brazil, the estimations indicate that about 140 thousand children are blind; among these, 15 to 20% are due to preventable causes. Among the measures to reduce these statistics is the Red Reflex Test (RRT), also known as "Teste do Olhinho", which consists of a quick and straightforward examination performed in the pediatric or ophthalmologist's office. In some states this test is performed even in the maternity ward. Objective: This study aimed to describe RRT's importance in the early detection of neonatal eye diseases and its impact on the specialized monitoring of diagnosed cases. Method: This is an integrative review of the scientific literature published between 2007 and April 2020 in the BVS (Biblioteca Virtual de Saúde), SCIELO, and PUBMED, using the descriptors: eye diseases, neonate, red reflex test;   with the help of the Boolean operator "and." Results: The first search released 467 articles aligned with the topic; 35 were excluded due to duplication in the databases, and 400 eliminated after inclusion criteria, leaving 35. Of them, ten studies that met inclusion and exclusion criteria were selected. Conclusion: The studies presented in this review ratify RRT's importance and its effectiveness in diagnosing vision diseases in neonates such as retinoblastoma, conjunctivitis, strabismus, congenital cataracts, retinopathies, uveitis, glaucoma, infections, birth trauma, and blindness.
Keywords: Eye diseases; Neonate; Red reflex test